Knowledge and Attitude about Management of Endodontically –Treated Teeth (ETT): A Survey Amongst Dental Practitioners in Benghazi, Libya - Khadiga Mohamed,; Khadiga Elfallah,; Hend Elkawash,; Nuha Elkadiki,; Eman Mohamed, (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Restoration of endodontically treated teeth is a controversial area, because the loss of structural integrity, leads to a higher possibility of fracture. Dentists should follow techniques to perform successful and durable prostheses by updating their knowledge about the new materials conducted to enhance their use and get the experience. The aim of this study was to evaluate the knowledge and attitude about the treatment of endodontically treated teeth among dental practitioners of Benghazi in Benghazi, Libya. Methods. Data collected through a self-administrative questionnaire designed to assess the knowledge of dentists in Benghazi about the management of endodontically treated teeth from a fixed prosthodontics restoration point of view. 150 questionnaires distributed among targeted dentists, and only 103 responded, with the required answers. All statistical analyses carried out at a significance level of P < 0.05. Results analyzed and compared using the ONE-WAY ANOVA. Results. The total sample was 103 which 69.9% were female dentists. About 31% of the dentists were aged between 35-39 years. About 30% of participants have an average of experience years between 10 to 14 in their field. There were no significant differences in all tested variables. Conclusion. The dental practitioners of Benghazi displayed a good level of knowledge and attitude about the management of endodontically treated teeth. For further proficiency, efforts made the practitioners to be aware of the advances in fixed prosthodontics practice through continuing education programs.